Global Financial Cycle, Household Credit, and Macroprudential Policies - Epure, Mircea; Mihai, Irina; Minoiu, Camelia; Peydró, José-Luis (Management Science, 2024)
We show that macroprudential policies dampen the impact of global financial conditions on local bank credit cycles. For identification, we exploit variation in the U.S. volatility index (VIX) and household and business credit registers in an emerging market economy in which banks depend on foreign funding and macroprudential measures vary over the full cycle. Our results suggest that when the VIX is low, tighter macroprudential policies reduce household lending, notably for riskier (foreign currency (FX) and high debt-service-to-income) loans and by banks dependent on foreign funding. Moreover, they increase (less regulated) local currency lending to real estate firms. Such periods are associated with less subsequent total lending to households and firms and with a lower share of FX loans at the local level. Consistently, when the VIX is low, tighter macroprudential policies dampen house prices and economic activity. This paper was accepted by Victoria Ivashina, finance. Funding: M. Epure acknowledges support from the Serra Húnter program. This project received funding from the European Research Council under the European Union’s Horizon 2020 research and innovation program [Grant 648398], from the Agencia Estatal de Investigacion [Grants PID2020-115660GB-I00 and PGC2018-102133-B-I00], and the Severo Ochoa Program for Centers of Excellence in Research and Development [Grant CEX2019-000915-S]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2024.4981 .